Atrazine Soil Core Residue Analysis from an Agricultural Field 21 Years after Its Ban. Issue 4 (1st July 2014) - Vonberg, David; Hofmann, Diana; Vanderborght, Jan; Lelickens, Anna; Köppchen, Stephan; Pütz, Thomas; Burauel, Peter; Vereecken, Harry
Abstract : Atrazine (2‐chloro‐4‐ethylamino‐6‐isopropylamino‐1, 3, 5‐triazine) groundwater monitoring in the Zwischenscholle aquifer in western Germany revealed concentrations exceeding the threshold value of 0.1 μg L −1 and increasing concentration trends even 20 yr after its ban. Accordingly, the hypothesis was raised that a continued release of bound atrazine residues from the soil into the Zwischenscholle aquifer in combination with the low atrazine degradation in groundwater contributes to elevated atrazine in groundwater. Three soil cores reaching down to the groundwater table were taken from an agricultural field where atrazine had been applied before its ban in 1991. Atrazine residues were extracted from eight soil layers down to 300 cm using accelerated solvent extraction and analyzed using liquid chromatography–tandem mass spectrometry. Extracted atrazine concentrations ranged between 0.2 and 0.01 μg kg −1 for topsoil and subsoil, respectively. The extracted mass from the soil profiles represented 0.07% of the applied mass, with 0.01% remaining in the top layer. A complete and instantaneous remobilization of atrazine residues and vertical mixing with the groundwater body below would lead to atrazine groundwater concentrations of 0.068 μg L −1 . Considering the area where atrazine was applied in the region and assuming instantaneous lateral mixing in the Zwischenscholle aquifer would result in a mean groundwater concentration of 0.002 μg L −1 . A conservative estimation suggests an atrazine half‐life value of about 2 yr for the soil zone, which significantly exceeds highest atrazine half‐lives found in the literature (433 d for subsurface soils). The long‐term environmental behavior of atrazine and its metabolites thus needs to be reconsidered.